A Review of and Recommendations for the Management of Patients With Life-Threatening Dabigatran-Associated Hemorrhage: A Single-Center University Hospital Experience. (December 2015) - Kumar, Rohit; Smith, Roy E.; Henry, Brian L.
Dabigatran is an oral direct thrombin inhibitor that is approved for the prevention of stroke and systemic embolism in nonvalvular atrial fibrillation. Dabigatran has several advantages over warfarin including predictable pharmacokinetics and pharmacodynamics which eliminates the need for routine laboratory monitoring, superiority over warfarin in preventing stroke, or systemic embolism without having an increased risk of bleeding. However, as with any anticoagulant, there remains a real chance of bleeding, including major or life-threatening hemorrhage. Many physicians feel comfortable managing bleeding complications on older anticoagulants like warfarin and heparin, due to extensive experience with the medications along with antidotes to reverse their effects as well as established protocols for treating anticoagulant-associated hemorrhage. However, most physicians have limited clinical experience with dabigatran, there is no specific antidote for dabigatran reversal and there is a paucity of protocols, guidelines, and recommendations for how to manage dabigatran-associated hemorrhage. In this review, we present a case series of patients admitted to our institution for management of bleeding while receiving dabigatran. We retrospectively reviewed these cases to evaluate the efficacy and rationale of the various anticoagulation reversal strategies employed in the context of the existing evidence found in the literature. Specific focus is placed on the therapies utilized and the coagulation studies used to manage these patients.